The Relationship Between Colorectal Cancer Screening Adherence and Knowledge Among Vulnerable Rural Residents of Appalachian Kentucky - Bardach, Shoshana H. (2012)
BACKGROUND: Colorectal cancer (CRC) is one of the leading causes of cancer related deaths among residents of rural Appalachia. Rates of guideline-consistent CRC screening in Appalachian Kentucky are suboptimal. OBJECTIVE: This study sought to determine the relationship between colorectal cancer screening knowledge, specifically regarding recommended screening intervals, and receipt of screening among residents of rural Appalachian Kentucky. METHODS: Residents of Appalachian Kentucky (n=1096) between the ages of 50 and 76 completed a telephone survey including questions on demographics, health history, and knowledge about colorectal cancer screening between November 20, 2009 and April 22, 2010. RESULTS: While 67% of respondents indicated receiving screenings according to guidelines, respondents also demonstrated significant knowledge deficiencies about screening recommendations. Nearly half of respondents were unable to identify the recommended screening frequency for any of the colorectal cancer screening modalities. Accuracy about the recommended frequency of screening was positively associated with screening adherence. CONCLUSIONS: Enhanced educational approaches have the potential to increase colorectal cancer screening adherence in this population and reduce cancer mortality in this underserved region. IMPLICATIONS FOR PRACTICE: Nurses play a critical role in patient education, which ultimately may increase screening rates. To fulfill this role, nurses should incorporate current recommendation about CRC screening into educational sessions. Advanced practices nurses in rural settings should also be aware of the increased vulnerability of their patient population and develop strategies to enhance awareness about CRC and the accompanying screening tests.